UiTM News Hub: Financial Literacy by BSN / Al-Amin Abdul Razi - Abdul Razi, Al-Amin (Universiti Teknologi MARA, Perak, 2022)
14 September 2022: The Administration Off ice has organized a Financial Literacy Program with BSN atDewan Ibnu Al-Khatib, Seri Iskandar Campus, UiTM Perak branch. Bank Simpanan Nasional (BSN) is a financial institution under the regulation of the Malaysian Ministry ofFinance (MOF) which is responsible for inculcating the habit of saving and managing finances wiselyamong Malaysians.